Attitudes and behaviour of general practitioners and their prescribing costs: a national cross sectional survey. Issue 1 (1st February 2003) - Watkins, C; Harvey, I; Carthy, P; Moore, L; Robinson, E; Brawn, R
Abstract : Background: General practitioner (GP) prescribing accounts for about 10% of NHS expenditure. GPs at the top of the range have annual prescribing costs that are almost twice as much as those at the bottom of the range. This variation cannot be accounted for purely in terms of differences in underlying need for health care. Objectives: To describe the relationship between GPs' prescribing costs and their attitudes towards prescribing decisions and prescribing information sources, and to identify potentially modifiable attitudinal and behavioural factors associated with high cost prescribing. Design: A postal questionnaire was designed on the basis of hypotheses developed from a literature search and an earlier qualitative survey. This questionnaire was sent to a national sample of GPs with equal numbers of practices in the upper, middle, and lowest quintile of prescribing costs. Setting: GP practices in England. Participants: 1714 GPs in NHS practice. Outcome measures: GPs' self-reported practices, attitudes and personal characteristics. Results: There was a 64% response rate. Responders were more likely to be from larger practices, in less deprived areas, and with lower prescribing costs than were non-responders. Multivariable analysis showed that GPs with high prescribing costs were significantly more likely to work in dispensing practices, in practices with low income populations, in single handed practices, and in practices without a GP trainer. They were also significantly more likely to see drug company representatives more frequently, to prescribe newly available drugs more freely, to prescribe more readily to patients who expect a prescription, to report high levels of frustration from lack of time in the consultation, to find unsatisfactory those consultations which ended in advice only, and to express dissatisfaction with their review methods for repeat prescribing. They were significantly less likely to find useful criticism of prescribing habits by colleagues, and to check the BNF rather than other sources when uncertain about an aspect of drug treatment. Conclusions: While they cannot be held to have a causal relationship, the pattern of attitudes towards prescribing of GPs in the highest quintile of prescribing costs provide the basis for developing an educational intervention which may be an acceptable method of modifying the attitudes of GPs and consequently reducing their prescribing costs.